Using the Internet to Improve Student Learning During the Covid 19 Pandemic - Rita Novita Sari; Ratna Sri Hayati; Ivi Lazuly (JUDIMAS, 2021)
Teaching and learning are activities carried out in accordance with the curriculum set by the government to help students to obtain a good education. Before the pandemic, the teaching and learning process was carried out offline (face to face) in classrooms with students and teachers. Since the Covid 19 pandemic entered Indonesia, the teaching and learning process was carried out online, namely at home. This teaching and learning process is carried out to break the chain of transmission of Covid 19 in Indonesia. The use of internet media in the teaching and learning process in the world of education during a pandemic is a way out, where students and teachers cannot carry out face-to-face learning. By using Google Classroom teachers can provide materials, assignments, and exercises by uploading them via Google Classroom, students can download materials, assignments and exercises that have been uploaded from Google Classroom.